Impact of HR practices on corporate image building in the Indian IT sector - Renu Rana; Shikha Kapoor; Sandeep Kumar Gupta (Problems and Perspectives in Management, 2021)
HR practices have been always significant for researchers and industries because of the large expansion of the companies in various fields, which requires leaders who can identify and introduce innovative and effective HR practices to utilize and retain human resources for the long period. In the 21st century, there has been tremendous growth in the IT sector all around the world. The Indian IT sector has become globally competitive and high-tech in the rapidly developing Indian economy. Hence, this study was undertaken in the Indian IT sector to identify the impact of HR practices on corporate image building. This paper applied a quantitative research method. Data from 100 respondents were collected with the help of a structured questionnaire to test the hypotheses. Pearson’s correlation coefficient and SPSS 20 software were used for data analysis. The findings of the regression analysis proved that there is a significant relationship between employer branding and corporate image building. The analysis of this study indicates that the IT companies implementing the HR practices based on employer branding and corporate social responsibility get benefits in building the corporate image and give positive results to them. HR practices have a significant relationship with corporate image building.